Heterobimetallic Mo–μ-O–M complexes (M = Co, Cu, Zn, Mn, Cd or Na) based on a flexidentate (Me3tacn)MoO3 metalloligand. (1st February 2023) - Cheng, Yao; Xu, Qian-Ya; Jiao, Yan-Ping; Qian, Bing-Feng; Jia, Ai-Quan; Zhang, Qian-Feng
Graphical abstract: The (Me3 tacn)MoO3 metalloligand coordinates with several metals forming six heterobimetallic complexes with different nuclearities (3–12) via one or two or three terminal oxygens. Abstract: The ligating properties of the neutral weakly-donating metalloligand [(Me3 tacn)MoO3 ] (Me3 tacn = 1, 4, 7-trimethyl-1, 4, 7-triazacyclononane) to form Lewis acid-base adducts toward six metal acetate salts has been explored in this paper. Six heterobimetallic complexes, [(Me3 tacn)MoO3 4 Co](BPh4 )2 (1 ), [(Me3 tacn)MoO3 2 Cu2 (CH3 COO)4 ] (2 ), [(Me3 tacn)MoO3 4 Zn](BPh4 )2 (3 ), [(Me3 tacn)MoO3 2 Mn(dmf)4 ](BPh4 )2 (dmf = N, N -dimethylformamide, 4 ), [(Me3 tacn)MoO3 4 Cd2 (CH3 COO)2 (CH3 OH)3 (H2 O)](BPh4 )2 (5 ) and [(Me3 tacn)MoO3 4 Na8 (μ-O)2 (μ3 -OH)2 ](BPh4 )2 (6 ), have been synthesized and characterized spectroscopically. The crystal structures of complexes 1 –6 were determined, showing the good ligating property and rich coordination modes of the [(Me3 tacn)MoO3 ] metalloligand.